TCR-T Immunotherapy: The Challenges and Solutions - Liu, Yating; Yan, Xin; Zhang, Fan; Zhang, Xiaoxia; Tang, Futian; Han, Zhijian; Li, Yumin (Frontiers in Oncology, 2022)
T cell receptor-engineered T cell (TCR-T) therapy is free from the limit of surface antigen expression of the target cells, which is a potential cellular immunotherapy for cancer treatment. Significant advances in the treatment of hematologic malignancies with cellular immunotherapy have aroused the interest of researchers in the treatment of solid tumors. Nevertheless, the overall efficacy of TCR-T cell immunotherapy in solid tumors was not significantly high when compared with hematological malignancies. In this article, we pay attention to the barriers of TCR-T cell immunotherapy for solid tumors, as well as the strategies affecting the efficacy of TCR-T cell immunotherapy. To provide some reference for researchers to better overcome the impact of TCR-T cell efficiency in solid tumors.